Solar cells based on heterostructures n-CdS/porous-Si/p-Si - Diadenchuk, Alona; Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Kidalov, V. V. (My University, 2017)
The paper presents the results of investigation of thin Cds films obtained by the surface chemical deposition method
Keywords: deposition method; surface chemical